Teens & Internet Safety - Kate Fogarty (EDIS)
FCS-2248, a 4-page fact sheet by Fate Fogarty, is one in a series of discussions on understanding teen sexuality. It defines online sexual solicitation and cyber-bullying, explains the risk factors and negative effects of these communications, and outlines ways to protect youth from harm. Published by the UF Department of Family Youth and Community Sciences, October 2006.